The baxters ebook A novel. - Kingsbury, Karen (Baxter Family, 2022)
Now an original series on Prime Video This warmhearted prequel to the "heart-tugging and emotional" ( RT Book Reviews ) #1 New York Times bestselling Baxter Family Series—now a television series—follows the family members as they face rising tensions during a wedding and a colossal storm. A terrible storm builds in the early morning sky over Bloomington, Indiana, as Elizabeth Baxter prepares to celebrate her daughter Kari's wedding to Tim Jacobs. It's supposed to be the happiest of days, but Elizabeth can't shake a growing sense of dread. Something bad is about to happen. Elizabeth knows it. Indeed, there are dark currents of conflict and doubt coursing through each of the Baxter family, and Kari Baxter is starting to panic. Is her decision to marry Tim a mistake? Meanwhile, Kari's brother Luke is angry and resentful of their sister Ashley, who has recently returned from Paris as a single mom. Everyone thinks Ashley spends too little time with her son, and they're upset with her for another reason: Ashley has rejected her loyal long-ago love, Landon Blake, who clearly still cares for her. At the same time, the four Baxter sisters are struggling with the faith that has always been the family's glue. When the storm outside reaches a terrifying crescendo, a shocking moment of danger brings important truths to light. At the end of the long day, can the Baxters remain a family, tested but stronger?